Membangun Infrastruktur Jaringan Bagi Siswa SMKN 13 Bandung - Imannudin Akbar; Arif Bakti Nugraha; R.Yadi Rakhman; Erlang Anggara Widjaksono (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2026)
This Community Service Program (PkM) aims to equip students of SMKN 13 Bandung with practical skills in Debian server administration. The activity was conducted through an intensive workshop emphasizing hands-on practice, aimed at enhancing students' abilities to build a network infrastructure based on Debian 12. This activity not only provided theoretical understanding but also prepared students for the Competency Skills Test (UKK) and challenges in the workforce. Through this program, students gained skills in configuring network services such as DNS, DHCP, Web Server, and Database Server using the Command Line Interface (CLI). Evaluations showed significant improvement in students' knowledge and skills, as well as their readiness to face exams and enter the workforce. This program is expected to enhance the quality of graduates from SMKN 13 Bandung, meeting the demands of the information technology industry.